Quantum metrology with nonclassical states of atomic ensembles - Pezze, Luca; Oberthaler, Markus K. (Reviews of modern physics, 2018)
Entanglement is the basis of quantum technologies aimed at revolutionizing measurements, computing, and communications. This article reviews methods to improve measurement precision and sensitivity by harnessing entangled states of many atomic probe particles. The achievements of different experimental entanglement schemes are presented with theoretical analyses of their fundamental and practical limits, discussing prospects for applications in clocks, frequency standards, and measurements of forces and fields.